Marginal abatement cost under the constraint of carbon emission reduction targets: An empirical analysis for different regions in China. (10th March 2020) - Wang, Zhaohua; Chen, Haitao; Huo, Ru; Wang, Bo; Zhang, Bin
Abstract: As the global climate and environmental issues become increasingly serious, low-carbon development has become a consensus among countries to seek new economic growth pathway. As an important emitter of carbon dioxide, China has put forward "Thirteenth Five-Year Plan" (TFYP) outline that carbon dioxide emissions per unit of gross domestic product (GDP) will be 18% lower in 2020 than that in 2015. To measure the policy effects on CO2 emission reduction and abatement costs, the directional distance function model is introduced in this paper, and the sensitivity analysis is conducted to verify the rationality of our index formulation. The results show the areas with the highest carbon emission control target level have significantly higher marginal abatement costs than that of other areas. In the short term, the reduction targets policy effect on decreasing carbon abatement cost is not significant. Through sensitivity analysis, we further discovered that the carbon emission reduction cost is less sensitive to the carbon emission reduction target, and the impact in the short term is smaller. However, as time goes by, the impact increases. We suggest that the government should guide interregional enterprises to cooperate and play a synergistic role. Implementing the multilevel emission reduction targets and expanding the scope of trading in the national carbon trading market are especially important to optimize the allocation. Highlights: China's average carbon marginal abatement cost will be 0.23 million yuan/ton in 2020 under the current scenario. Setting low emission reduction targets can not significantly reduce carbon marginal costs in the short term. Improving the production efficiency of cities with low and medium emission levels is important for China's sustainable development.